Age- and gender-related development of stretch shortening cycle during a sub-maximal hopping task - G Laffaye; MA Choukou; N Benguigui; J Padulo (Termedia Publishing House, 2016)
The aim of this study was to analyse the effects of age and gender (and their interaction) on a stretch shortening cycle solicited during a hopping task. For this aim, 147 girls and 148 boys aged 11 to 20 years, who were enrolled in middle school or secondary school with no experience in sport activity, or training less than three times per week, performed 3x5 hops in place. Leg-stiffness, jump-height and reactive-strength indices were assessed using an accelerometer (Myotest). The participants were selected in order to form five age groups: 11 12, 13-14, 15-16, 17-18 and 19-20 years. Regression analysis between force and centre of mass displacement revealed spring-mass behavior for all groups (r2=73-89), meaning that beginning at the age of 11 years, children are able to perform complex inter-muscular coordination of the lower limbs, revealing efficient neural control early in childhood. Leg stiffness increased from 24.7 ± 10.6 kN • m-1 at 11-12 years to 44.1 ± 14 kN • m-1 in boys, with a small increase until 16 years (+17%) and a large increase between 17 and 20 years (+32.7%). In girls, leg stiffness increased from 26.6 ± 9 kN • m-1 at 11-12 years to 39.4 ± 10.9 kN • m-1 at 19-20 years, with a curious decrease in leg stiffness at 17-18 years, probably due to an increase in the percentage of fat at this age (25%). While no gender effect was found, the reactive-strength index revealed that, from 15-16 years onward, boys were better able to produce high levels of force in a shorter time than girls. The age of 15-16 years is a threshold of maturity and gender differentiation, where the boys investigated are more efﬁcient in the stretch shortening cycle.